Astrogliosis and HSP 70 activation in neonate rats' brain exposed to sodium metavanadate through lactation - Cuesta, Santiago (2013)
The effect of sodium metavanadate (NaVO3) exposure on lipid oxidative damage in the CNS of suckling rats was studied. Using histological markers of cellular injury, we also studied the morphological alterations of neurons and astroglial cells in different regions of neonate rats CNS after NaVO3 exposure. Dams of treated litters were intraperitoneally injected with 3 mg NaVO3/kg body weight/day during 12 days starting on post-natal day (PND) 10. On the 21st PND, four pups of each litter were sacrificed by decapitation and six brain areas were removed for lipid peroxidation assay by the thiobarbituric acid (TBA) reaction, the other four were transcardially perfused-fixed and their brains were removed and cut with a cryostat. Brain sections were processed for: NADPHd histochemistry and anti-HSP70, anti-GFAP and anti-S100 immunohistochemistry. The relative optical density of the NADPHd stained layers and of S100 (+) astrocytes and the GFAP (+) astrocyte surface area in Cer and Hc were measured. Although MDA levels, S100 immunostaining and NADPHd activity didn't show differences between experimental and control groups, both astrogliosis and HSP70 activation were detected in Cer, while only the former was detected in Hc of V-exposed pups.